[PP.11.09] CARDIOVASCULAR RISK ASSESSMENT, CLINICAL CHARACTERISTICS, AND COMORBIDITIES OF HOSPITALIZED PATIENTS WITH HYPERTENSION AND ACID-BASE DISORDERS. (September 2017) - Olteanu, D.; Suta, T.; Ungureanu, R.; Dediu, G.; Diaconu, C.; Balaceanu, A.
Abstract : Objective: The aim of the study was the assess the cardiovascular risk of the hospitalized patients with hypertension and acid-base disorders. Design and method: The retrospective study included 109 patients with hypertension and acid-base disorders admitted to clinical emergency hospital between August-November 2016. Results: The average age was 73.64 years ± 11.39. The minimum age was 43 and maximum age were 97. From 109 patients 52.29% were female and 47.70% were male.The following distribution in patients with high blood pressure was noticed: grade I: 23.85%; grade II: 38.53%; grade III: 32.11%. Comorbidities: Chronic kidney disease evaluated by MDRD equation was encountered in 83.49% cases; grade II 26.60%; grade III 39.44%; grade IV 11.00%. Hypertrophic cardiomyopathy with echocardiographic diastolic dysfunction was presented at 36.69% patients; from these patients electrocardiographic signs of left ventricle hypertrophy were found in 1.83% cases. Diabetes mellitus appeared in 21.10% cases. From female patients 43.11% had CKD and from male patients 39.44% had CKD. According to European Score charts the patients included in our study are distributed following the next categories: low risk 4.52%; medium risk 38.53%, high risk 27.52% and very high risk 11.92%. From the total of our patients, only 68.79% had presented acid-base disorder as it follows: 5.50% metabolic alkalosis, 22.93% metabolic acidosis, 1.83% respiratory alkalosis and 38.53% respiratory acidosis. 59.63% of the patients with acid-base disorder had a medium, high or very high risk of cardiovascular disease. Hypercapnia was diagnosed in 35.77% of the patients, while hypoxia appeared in 72.47% of them. 33.02% of the patients had developed both hypercapnia and hypoxia. Conclusions: The majority of the patients with hypertension and acid-base disorders had a medium, high and very high risk of cardiovascular disease. CKD was the most common comorbidity at these patients.